2003
DOI: 10.1063/1.1630843
|View full text |Cite
|
Sign up to set email alerts
|

Absolute densities of N and excited N2 in a N2 plasma

Abstract: Agarwal, S.; Hoex, B.; van de Sanden, M.C.M.; Maroudas, D.; Aydil, E.S.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
44
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 71 publications
(46 citation statements)
references
References 20 publications
2
44
0
Order By: Relevance
“…These highly reactive species can affect the surface and thus deposition chemistry, especially the properties of the deposited thin film of GaN depend on the concentration of N and excited N 2 species during the film growth. (7) The main aim of this work is to obtain reliable information about the concentration of the active species (significant atoms, molecules and ions) of N 2 plasma, which determine the nitridation process in the plasma reactor and then to adjust optimum discharge conditions for the desired treatment of the samples in a simple and cost-effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…These highly reactive species can affect the surface and thus deposition chemistry, especially the properties of the deposited thin film of GaN depend on the concentration of N and excited N 2 species during the film growth. (7) The main aim of this work is to obtain reliable information about the concentration of the active species (significant atoms, molecules and ions) of N 2 plasma, which determine the nitridation process in the plasma reactor and then to adjust optimum discharge conditions for the desired treatment of the samples in a simple and cost-effective manner.…”
Section: Introductionmentioning
confidence: 99%
“…The radical wall loss time which is an important model input parameter is determined by monitoring the radical density in the temporal afterglow of the plasma with ionization threshold mass spectroscopy (ITMS) [47][48][49][50][51][52][53] . This technique takes advantage of the fact that the threshold energy for direct ionization of a radical, e.g., e − + N → N + + 2e − is lower than the threshold energy for the corresponding dissociative ionization of the mother molecules leading to the same ion, e.g., e − + N 2 → N + + N + 2e − .…”
Section: F Radical Wall Loss Timesmentioning
confidence: 99%
“…[1][2][3][4] It is capable of detection of a variety of lowdensity reactive gas phase species at a substrate position without the limitations, inherent to some of the optical techniques, such as the existence of suitable optical transitions of the radical or the molecule of interest. TIMS has been successfully applied for the radical density measurements, for example, in SiH 4 -CH 4 -H 2 glow discharge plasma, 2 Cl 2 plasma used for Si etching, 5 O 2 and N 2 plasmas, 1, 6 and hot filament diamond chemical vapor deposition ͑CVD͒.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, Agarwal et al reported TIMS measurement of absolute densities of electronically excited N 2 in an inductively coupled N 2 plasma. 6 Although TIMS is a versatile technique, it requires a carefully designed differentially-pumped housing for the quadrupole mass spectrometer ͑QMS͒ and a proper calibration procedure to accurately determine the absolute number density of the radicals. Knowledge of the absolute density of various reactive species in a plasma is essential for the validation of plasma chemistry models, since their results are often dependent on unknown reaction rates and reaction branching ratios.…”
Section: Introductionmentioning
confidence: 99%